2020
DOI: 10.1021/acs.jafc.0c04605
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Glycome and Glycoproteome of Bovine Milk-Derived Exosomes

Abstract: Bovine milk-derived exosomes (BMDEs) have potential applications in the pharmaceutical industry as drug delivery carriers. A comprehensive analysis of protein glycosylation in exosomes is necessary to elucidate the process of targeted delivery. In this work, free oligosaccharides (FOSs), O-glycans, and N-glycans in BMDEs and whey were first analyzed through multiple derivation strategies. In summary, 13 FOSs, 44 O-glycans, and 94 N-glycans were identified in bovine milk. To analyze site-specific glycosylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…In total, 30, 42, 32, 34, and 35 OSs were identified in bovine, caprine, ovine, camel, and human milk, respectively. Most of the OSs found in different species were consistent with previous studies, ,,,,,,, , and some OSs that have not been reported before were also found in our study, which were marked in Table . It is worth mentioning that almost all the reported OSs in the ovine milk were also detected in our study, besides these, the other 13 OSs detected in our study were discovered for the first time.…”
Section: Resultssupporting
confidence: 93%
“…In total, 30, 42, 32, 34, and 35 OSs were identified in bovine, caprine, ovine, camel, and human milk, respectively. Most of the OSs found in different species were consistent with previous studies, ,,,,,,, , and some OSs that have not been reported before were also found in our study, which were marked in Table . It is worth mentioning that almost all the reported OSs in the ovine milk were also detected in our study, besides these, the other 13 OSs detected in our study were discovered for the first time.…”
Section: Resultssupporting
confidence: 93%
“…For global peptides, the elution gradient was set as follows: 0–8 min, 3% B; 8–88 min, 8% B; 88–110 min, 28% B; 110–115 min, 32% B; 115–120 min, 80% B. Other mass spectrometry parameters were performed according to methods previously established in our laboratory [ 19 ]. For glycopeptides, the gradient elution was 2–6% B, 1 min; 6–30% B, 90 min; 30–38% B, 22 min; 38–80% B, 5 min; and 80% B, 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Intact glycopeptides (IGPs) were enriched as described previously [ 44 ]. IGPs were desalted, resuspended and then analyzed using nanoLC-MS system.…”
Section: Methodsmentioning
confidence: 99%
“…IGPs were desalted, resuspended and then analyzed using nanoLC-MS system. LC conditions and MS parameters for IGPs were described previously [ 44 ]. Results were filtered based on the following criteria: (1) a false discovery rate (FDR) less than 1% for glycoproteins and (2) each peptide spectra matches (PSM) annotated by at least one N-linked glycan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation